Identification and Validation of Compounds Targeting Leishmania major Leucyl-Aminopeptidase M17 - Aguado, Mirtha E; Carvalho, Sandra; Valdés-Tresanco, Mario E; Lin, De; Padilla-Mejia, Norma; Corpas-Lopez, Victoriano; Tesařová, Martina; Lukeš, Julius; Gray, David; González-Bacerio, Jorge; Wyllie, Susan; Field, Mark C (ACS infectious diseases, 2024)
Leishmaniasis is a neglected tropical disease; there is currently no vaccine and treatment is reliant upon a handful of drugs suffering from multiple issues including toxicity and resistance. There is a critical need for development of new fit-for-purpose therapeutics, with reduced toxicity and targeting new mechanisms to overcome resistance. One enzyme meriting investigation as a potential drug target in Leishmania is M17 leucyl-aminopeptidase (LAP). Here, we aimed to chemically validate LAP as a drug target in L. major through identification of potent and selective inhibitors. Using RapidFire mass spectrometry, the compounds DDD00057570 and DDD00097924 were identified as selective inhibitors of recombinant Leishmania major LAP activity. Both compounds inhibited in vitro growth of L. major and L. donovani intracellular amastigotes, and overexpression of LmLAP in L. major led to reduced susceptibility to DDD00057570 and DDD00097924, suggesting that these compounds specifically target LmLAP. Thermal proteome profiling revealed that these inhibitors thermally stabilized two M17 LAPs, indicating that these compounds selectively bind to enzymes of this class. Additionally, the selectivity of the inhibitors to act on LmLAP and not against the human ortholog was demonstrated, despite the high sequence similarities LAPs of this family share. Collectively, these data confirm LmLAP as a promising therapeutic target for Leishmania spp. that can be selectively inhibited by drug-like small molecules.
Keywords: M17 leucyl-aminopeptidase; drug discovery; target validation; Leishmania donovani; Leishmania major; zvířata; Humans; RapidFire-MS; Protozoan Proteins; Antiprotozoal Agents; protozoální proteiny; Leishmania; lidé; antiprotozoální látky; Animals